PENERAPAN SISTEM OPERASI SWIFT UNTUK MEMBUAT APLIKASI E-COMMERCE PADA APPLE IOS - Zaki Dony Karensyah (2022)
E-Commerce application is an application that is a place for people to meet their daily needs. People's shopping habits that have changed from offline to online have made application developers develop E-Commerce applications that can meet their needs. This study aims to create a swift-based E-Commerce application that was developed with the help of a data processing application, namely X-Code. Apple itself is known for its very reliable security features. So that it is hoped that it can protect user data from the threat of leakage and theft of personal data that is rife. Based on the results of research that has been done. Swift-based E-Commerce applications can be a new breakthrough in the digital world. Applications made on a swift basis can minimize bugsss and errors that occur with Apple iOS users. This is because the source code is compatible and developed only for Apple, so it is more suitable for use with other Apple devices.